2016
DOI: 10.1186/s13019-016-0437-8
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic hypothermia in adult patients receiving extracorporeal life support: early results of a randomized controlled study

Abstract: Cardiac arrest with cerebral ischaemia frequently leads to severe neurological impairment. Extracorporeal life support (ECLS) has emerged as a valuable adjunct in resuscitation of cardiac arrest. Despite ECLS, the incidence of permanent neurological injury remains high. We hypothesize that patients receiving ECLS for cardiac arrest treated with therapeutic hypothermia at 34 °C have lower neurological complication rates compared to standard ECLS therapy at normothermia. Early results of this randomized study su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 12 publications
1
31
0
2
Order By: Relevance
“…After excluding the duplicated papers, review or meeting abstracts, and irrelevant articles, 60 articles were left for further screening by checking the full texts. 47 articles were excluded, of which, seven were overlapped studies [42][43][44][45][46][47][48], seven were performed in pediatric patients [49][50][51][52][53][54][55], two study contained patients with other disease besides CA and the data related to CA could not be obtained separately [16,56], three studies contained CA patients treated with other methods besides ECPR and the data related to ECPR could not be obtained separately [17,57,58], fifteen studies had no sufficient data [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73], and eleven studies only had therapeutic hypothermia arms (without controls) [37,[74][75][76][77][78][79][80][81][82][83]. Two...…”
Section: Discussionmentioning
confidence: 99%
“…After excluding the duplicated papers, review or meeting abstracts, and irrelevant articles, 60 articles were left for further screening by checking the full texts. 47 articles were excluded, of which, seven were overlapped studies [42][43][44][45][46][47][48], seven were performed in pediatric patients [49][50][51][52][53][54][55], two study contained patients with other disease besides CA and the data related to CA could not be obtained separately [16,56], three studies contained CA patients treated with other methods besides ECPR and the data related to ECPR could not be obtained separately [17,57,58], fifteen studies had no sufficient data [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73], and eleven studies only had therapeutic hypothermia arms (without controls) [37,[74][75][76][77][78][79][80][81][82][83]. Two...…”
Section: Discussionmentioning
confidence: 99%
“…Estudo controlado randomizado evidenciou que a realização da RCP assistida pelo Suporte de Vida Extracorpóreo (SVEc) trouxe melhoras à sobrevivência e aos desfechos neurológicos em comparação com o RCP convencional. A hipotermia terapêutica a 33°C mantida durante 24 horas em conjunto com o SVEc foi utilizada para 24 pacientes, dos quais 13 (54%) foram desmamados com sucesso e 12 (50%) receberam alta hospitalar com recuperação neurológica total [27].…”
Section: Fatores Predisponentes De Resultados Neurológicos Após Hipotermia Terapêuticaunclassified
“…Após leitura do resumo de cada artigo, selecionaram-se apenas os que mais traziam contribuições sobre o uso da hipotermia induzida, sendo escolhidos 16 [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] artigos.…”
Section: Methodsunclassified
“…However, unintentional sustained hypothermia may be due to dysfunction of central nervous system thermoregulation as a result of severe brain injury from cardiac arrest. An early report from an ongoing trial of therapeutic hypothermia versus normothermia for adults resuscitated with ECPR suggests that therapeutic hypothermia can be administered safely in this situation although findings about the effects on neurologic outcome from the trial have not yet been reported (42).…”
Section: Discussionmentioning
confidence: 99%